Development of autosensing for self-protection device based IOT - Seok Kim, Bong (International Journal of Engineering and Technology, 2018)
Background/Objectives: There is the needs for the service not only to keep a user informed of access to potentially dangerous people approaching from the rear by alarm sound or vibration through automatic sensor installed the device but to transmit location as well as sensing time to guardian through smartphone appwhen women are going off the beaten track on the way home late at nightMethods/Statistical analysis :It is composed of app that is interlocked with a protection device installed human body detection sensor and camera capable of autosensing potentially dangerous people approaching according to proximity sensor. This autodetection makes it possible not only to inform user on approaching the people by alarm sound as well as vibration but to transmit sensor detecting time and location to guardian.Findings: Self-protection device based IoT which not only is informed approaching a dangerous person by alarm and vibration using a device attached sensor in case of sensing the peopleâ€™s approaching but catches danger through smartphone application to take a picture and images included time and location is developed in this study.Improvements/Applications: This device will be expected to use not only women but students who are bullied at school. Pictures at school violence are transmitted to guardian if the student who has a device attached to the front of himmay occur school violence. Other improvements including if the device is dropped or handled roughly are under active consideration to send pictures or explanation of situation for guardian.Â Â